2018
DOI: 10.1039/c7cs00587c
|View full text |Cite
|
Sign up to set email alerts
|

Up in the air: oxygen tolerance in controlled/living radical polymerisation

Abstract: The requirement for deoxygenation in controlled/living radical polymerisation (CLRP) places significant limitations on its widespread implementation by necessitating the use of large reaction volumes, sealed reaction vessels as well as requiring access to specialised equipment such as a glove box and/or inert gas source. As a result, in recent years there has been intense interest in developing strategies for overcoming the effects of oxygen inhibition in CLRP and therefore remove the necessity for deoxygenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
353
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(360 citation statements)
references
References 247 publications
3
353
1
3
Order By: Relevance
“…Structurally,Z nOETPP possesses eight ethyl substituents in the b-carbon positions of the pyrroles as well as the four phenyl substituents in the meso positions.T ominimize the steric interactions,the pyrroles and its substituents tilt above and below the central plane of the porphyrin in an alternating fashion while the phenyls rotate into the macrocycle plane (Supporting Information, Video 1). [6] Kinetic investigation of N,N-dimethylacrylamide (DMA) under aerobic conditions revealed that the polymerization progressed in al inear fashion after as hort (ca. [16] With an expectation that ZnOETPP would behave similarly to the previously studied ZnTPP, [16] we examined its oxygen tolerance capabilities as as tarting point by polymerizing in the presence (Supporting Information, Table S1, entry 1) and absence (Supporting Information Table S1, entry 2) of air.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally,Z nOETPP possesses eight ethyl substituents in the b-carbon positions of the pyrroles as well as the four phenyl substituents in the meso positions.T ominimize the steric interactions,the pyrroles and its substituents tilt above and below the central plane of the porphyrin in an alternating fashion while the phenyls rotate into the macrocycle plane (Supporting Information, Video 1). [6] Kinetic investigation of N,N-dimethylacrylamide (DMA) under aerobic conditions revealed that the polymerization progressed in al inear fashion after as hort (ca. [16] With an expectation that ZnOETPP would behave similarly to the previously studied ZnTPP, [16] we examined its oxygen tolerance capabilities as as tarting point by polymerizing in the presence (Supporting Information, Table S1, entry 1) and absence (Supporting Information Table S1, entry 2) of air.…”
mentioning
confidence: 99%
“…To our amazement, only the nondeoxygenated reaction achieved polymerization with an excellent agreement between the theoretical and experimental (GPC) molecular weights (M n ), and an arrow molecular weight distribution (MWD, M w /M n = 1.09). [17] To test this hypothesis,w ea dded triethylamine (TEA) at 1equivalence to the trithiocarbonate for the polymerization of MA under both aerobic and anaerobic conditions (Supporting Information, Table S1, entries 5,6). [6] Kinetic investigation of N,N-dimethylacrylamide (DMA) under aerobic conditions revealed that the polymerization progressed in al inear fashion after as hort (ca.…”
mentioning
confidence: 99%
“…13 For instance, Chapman et al. elegantly used enzymes, such as glucose oxidase (GOx), to effectively deoxygenate traditional RAFT polymerizations 14, 15.…”
mentioning
confidence: 99%
“…However, almost no investigations have involved the use of oxygen in redox‐initiated radical polymerization reactions. In recent years and in response to demands from industry, a growing number of oxygen‐tolerant polymerization techniques have been developed ,. Most of these reactions were conducted at room temperature via redox initiation.…”
Section: Introductionmentioning
confidence: 99%